Leadership Style of Senior Manager of Medical Device Industry in Germany: A Case Study - Kousihan, Suriyakumaran; Elsaman, Hosam Azat; Maricar, Mohamed Ali (JPAIR Multidisciplinary Research, 2021)
Leadership allows organizations to focus on employee development and sustain efforts for well-being. It argued that the medical device industry is complex and leadership requires support to meet the demands. Moreover, increasing globalization and politicization of social welfare institutes have increased challenges. Regulatory compliance must be followed. The study aimed to explore the leadership style of senior leaders in the context of regulatory compliance in the medical device industry after the Covid-19 outbreak. The research objective is to get insight, thoughts, and shared experiences from the medical device industry leaders as they face regulatory challenges. The research used a qualitative approach and the data was collected through conducting interviews with medical device industry leaders and later performing a thematic analysis of the interview transcripts. The sample population taken in the research comprised 14 senior leaders from South Germany, particularly in Baden-Württemberg Region, where they shared their responses based on design questions. The questions were designed within the context of regulatory compliance. Ethical considerations maintain the anonymity of the participant. It was observed that regulatory compliance in the medical device industry has uncertain and dynamic situations where an authoritarian style of leadership becomes necessary. However, most of the leaders disagreed with this style of leadership and some resort to a democratic way of listening through effective communication or collaboration. Communication skill was found to be the most effective for leaders in the medical device industry. Leaders build personal relationships with their subordinates and try to cater to their needs.